ILHAS DE RACIONALIDADES NO ENSINO DE FÍSICA PARA A EDUCAÇÃO DE JOVENS E ADULTOS - Monaretto, Adriano (2018)
The principle of physics is usually based on the articulation of concepts, laws and theories and that by itself the direct approach on book forms of these contents can take the student to discourage and hinder the proper learning of concepts. This work was idealized aiming an alternative to overlap these difficulties, in order to contribute to the Teaching and Learning process, we propose a methodology that aided at the process of experimentation that is the Rationalities Islands - RI Methodology Gérard Fourez, by which we got significant results with the application of tree experiments with this methodology. As the result was considered positive, we decided that as a educational product of the Professional Masters choose to carry out a dissemination and investigation about the acceptability of the Methodology of Islands of Rationalities with the Physics and Sciences professors of the Regional Nucleus of Pato Branco – PR. We devised a course with the following title, "Islands of Rationalities in Physics Teaching: A Proposal for Teacher Training for Young and Adult Education", which was carried by MOODLE platform, seeking to reinforce the importance of experimentation in Physics and Sciences teaching, making possible organize experimentation scripts with an approach based on the RI theoretical and methodological proposal, a proposal very well accepted by the professors. But, having traditional obstacles like the questions of time and lack of space to carry the experimentation, just like expected.